The Experimental Evaluation of Cone Wedge Shape based Electronic Wedge Brake Mechanism in Vehicle Braking System - Sharil Izwan Haris; Fauzi Ahmad; Mohd Hanif Che Hassan; Ahmad Kamal Mat Yamin (Automotive Experiences, 2022)
The brake system is one of the most critical parts of a vehicle's technology for avoiding accidents. The ultimate focus of the braking system is to guarantee that adequate stopping force is available to stop the vehicle's longitudinal movement. Therefore, the ability of a brake system to stop a vehicle must be examined in terms of analyzing the brake system's performance and the implementation of the brake system on actual vehicles. This study offers a performance evaluation of the Electronic Wedge Brake based on the Cone Wedge Shape (CW-EWB) on the vehicle brake systems. The evaluation was carried out through dynamic assessments, namely sudden braking tests at constant speeds of 40, 60, and 90 km/h using the MATLAB Simulink software simulation method and an experimental study using hardware-in-loop simulation (HILS). In the simulation study, the performance of the vehicle brake system using CW-EWB was compared with the brake performance of the vehicle using the conventional hydraulic brake (CHB). The results showed that CW-EWB behaved similarly to the hydraulic brake in terms of required brake torque output but with a faster response time, i.e., between 0.5 – 1 s. The HILS experimental study was conducted to evaluate the performance of the CW-EWB on actual vehicles. This method confirmed the HILS results against the simulation results with a variable response time of less than 6%. Vehicle body speed, wheel speed, longitudinal tire slip, and stopping distance experienced by the vehicle were all evaluated. The study's findings show that the proposed CW-EWB is quite effective and sufficiently dependable to be used as a vehicle brake system, notably in Antilock Braking Systems.